On the Origin of Strategy: Action and Cognition over Time - Gavetti, Giovanni; Rivkin, Jan W. (Organization Science, 2007)
We develop a perspective on how managers search for a strategy. In the spirit of Cyert and March (1963), we aim for a perspective that reflects the reality of managerial behavior, that respects both the reasoning power of managers and the bounds on their rationality, and that permits organizations to change but within realistic limits. Our perspective employs the variable time to frame the question of strategy’s origins in a distinctive way. Over time, the cognitive and physical elements that make up a strategy become less plastic, while mechanisms to search rationally for a strategy become more available. This generates a fundamental tension in the origin of strategy: Managers struggle to understand their environment well enough to search rationally for an effective strategy before their firms lose the plasticity necessary to exploit that understanding. A focus on time allows us to synthesize and extend the evolutionary and positioning models of strategic search. Toward this end, we couple induction and deduction. The inductive part of the paper uses detailed observation of the search for a strategy at one firm to identify constructs that play a crucial role in strategic search. The deductive part steps beyond our focal firm and uses these constructs to derive theoretical propositions about the typical path of strategic search and the mortality associated with different approaches to search.